Effect of Previous Calcium Hydroxide Dressing on the Sealing Properties of the New Endodontic Cement Apical Barrier - Bidar, Maryam; Disfani, Reza; Gharagozlo, Salman; Rouhani, Armita; Forghani, Maryam (European Journal of Dentistry, 2011)
Objectives: Using the fluid filtration method, an in vitro study was conducted to evaluate the effects of medication with calcium hydroxide on the sealing ability of the New Endodontic Cement (NEC) apical barrier in the short and long terms. Methods: Fifty extracted single rooted teeth were prepared and apical resorption produced using acid sulfuric for four days. The teeth were randomly divided into two experimental groups (n=20) and two control groups. In group 1, calcium hydroxide was placed into all canals for one week and in group 2, no medication was used. In both groups, a 4 mm NEC apical plug was placed in the canals and the remaining portion of the canals was filled with gutta-percha. The amount of microleakage of all samples was evaluated after one week and three months. The data were statistically analyzed using two-way ANOVA. Results: There was no significant difference between the two groups in either time period (P>.05). In both group 1 and group 2, microleakage increased after three months but this increase was not statistically significant (P>.05). Conclusions: According to the result of this study, medication with calcium hydroxide had no adverse effect on the short- and long-term sealing properties of an NEC apical plug. (Eur J Dent 2011;5:260-264)
Keywords: Calcium hydroxide; Apical barrier; Leakage; Fluid filtration; New Endodontic Cement